1989
DOI: 10.1002/pd.1970090903
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of fetal glioblastoma multiforme

Abstract: Intracerebral tumours of the fetus are very rare conditions, most often presenting clinically as polyhydramnios and hydrocephalus. These conditions can be diagnosed with ultrasound and clearly differentiated from hydrocephalus and other intracranial lesions. The following report is of a case of an intracerebral tumour (glioblastoma multiforme) diagnosed at 33 weeks in utero using ultrasound. The prognosis for this condition is universally poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 7 publications
(9 reference statements)
0
18
1
1
Order By: Relevance
“…Polyhydramnios may be present, presumably secondary to difficulty swallowing. 4,13 Our case is unusual compared with prior reports in that instead of a single echogenic lesion, there were multifocal areas of increased echogenicity. To our knowledge the pronounced color flow appearance on sonography has not been described in other reported cases.…”
Section: Discussioncontrasting
confidence: 47%
“…Polyhydramnios may be present, presumably secondary to difficulty swallowing. 4,13 Our case is unusual compared with prior reports in that instead of a single echogenic lesion, there were multifocal areas of increased echogenicity. To our knowledge the pronounced color flow appearance on sonography has not been described in other reported cases.…”
Section: Discussioncontrasting
confidence: 47%
“…:Hi Most of the congenital intracranial tumors reported in the literature have been diagnosed in the third trimester: three of four teratomas after 28 weeks' gestation2 and five of five cases of glioblastomas after 30 weeks' gestation.3. 6 As in our case, four of five prenatally diagnosed glioblastomas A review of the five previously published cases of fetal glioblastomas showed quite uniform ultrasonographic findings: a large homogeneous hyperechoic mass involving the supratentorial cerebral parenchyma, except for one case in which a hypoechoic component was described within the lesion.u Mass effect and hydrocephalus were present in all cases. Our case had a lesion in a purely intraventricular location.…”
Section: Discussionmentioning
confidence: 77%
“…The other clinical sign is hydramnios [2,4,5], which is probably caused by decreased fetal swallowing due to hypothalamic dysfunction [6]. In this case, however, biophysical parameters, including amniotic fluid volume, were normal.…”
Section: Discussionmentioning
confidence: 82%
“…Most of the fetal intracranial tumors are diagnosed with a large head [1][2][3][4][5]. The other clinical sign is hydramnios [2,4,5], which is probably caused by decreased fetal swallowing due to hypothalamic dysfunction [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation